Host and environmental factors that influence plasmodium knowlesi malaria infection in humans: a systematic review - Michal Christina Steven; Glen Wendel Sibadogil; Syed Sharizman Syed Abdul Rahim; Richard Avoi; Fredie Robinson; Awang Setia Musleh; Mohammad Saffree Jeffree; Mohd Rohaizat Hassan (Borneo Epidemiology Journal, 2020)
Introduction: Plasmodium knowlesi(P.knowlesi) is a zoonotic malaria parasite, transmitted between non-human primate hosts by the Anopheles (An.) mosquitos, and causing spill-over infections in humans where the parasite, vector, host, and human converge.